Early immune innate hallmarks and microbiome changes across the gut during Escherichia coli O157: H7 infection in cattle - Larzabal, Mariano; Marques Da Silva, Wanderson; Multani, Anmol; Vagnoni, Lucas Emilio; Moore, Prando Dadin; Marin, Maia Solange; Riviere, Nahuel Agustin; Delgado, Fernando Oscar; Vilte, Daniel Alejandro; Romero Victorica, Matias; Tao, Ma; Luo, Le Guan; et al. (SpringerNature, 2021)
The zoonotic enterohemorrhagic Escherichia coli (EHEC) O157: H7 bacterium causes diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome (HUS) in humans. Cattle are primary reservoirs and EHEC O157: H7; the bacteria predominately inhabit the colon and recto-anal junctions (RAJ). The early innate immune reactions in the infected gut are critical in the pathogenesis of EHEC O157: H7. In this study, calves orally inoculated with EHEC O157: H7 showed infiltration of neutrophils in the lamina propria of ileum and RAJ at 7 and 14 days post-infection. Infected calves had altered mucin layer and mast cell populations across small and large intestines. There were differential transcription expressions of key bovine β defensins, tracheal antimicrobial peptide (TAP) in the ileum, and lingual antimicrobial peptide (LAP) in RAJ. The main Gram-negative bacterial/LPS signaling Toll-Like receptor 4 (TLR4) was downregulated in RAJ. Intestinal infection with EHEC O157: H7 impacted the gut bacterial communities and influenced the relative abundance of Negativibacillus and Erysipelotrichaceae in mucosa-associated bacteria in the rectum. Thus, innate immunity in the gut of calves showed unique characteristics during infection with EHEC O157: H7, which occurred in the absence of major clinical manifestations but denoted an active immunological niche.